関東地方における夏季地表オゾン濃度のNOx，VOC排出量に対する感度の地理分布 - 井上 和也; 安田 龍介; 吉門 洋; 東野 晴行 (大気環境学会誌, 2010)
To determine reasonable emission reduction measures for the mitigation of photochemical oxidant (ozone) pollutions over the Kanto area, it is important to know whether the sensitivity of the ozone concentration to precursor emissions is VOC-sensitive or NOx-sensitive at each location. Using a three-dimensional chemical transport model (CTM), we estimated the spatial distribution of the sensitivity regimes for the daily maximum ozone concentrations at each location over the Kanto area for a total of three days on which warning-level ozone was formed within the Kanto area. The Biogenic VOC (BVOC) emission amounts, input to the CTM, were estimated by considering recent emission measurements for Japanese native plant species. The results showed the sensitivity regime was VOC-sensitive over the limited regions near or within the urban center and was NOx-sensitive over most regions including the areas which had many warning-level ozone concentration days. On the other hand, the simulation results obtained using previous lower BVOC emission estimates showed that the regions with VOC-sensitive regimes significantly increased, indicating that the BVOC emission amounts input to the CTM significantly affects the estimated ozone concentration sensitivity regimes. 関東地方の光化学オキシダント（オゾン）汚染を軽減させるための合理的な排出削減対策を決定するためには，各地点におけるオゾン濃度の前駆物質排出量に対する感度がNOx-sensitive，VOC-sensitiveのいずれの状態（感度レジーム）にあるのかを知ることが重要である。本研究では，関東地方内で注意報発令レベルのオゾンが出現した夏季の複数日（合計3日間）について，3次元化学輸送モデルによるシミュレーションによって，関東地方における地点ごとのオゾン日最高濃度に対する感度レジームの地理分布を推定した。ここで，モデルに入力する植物起源VOC排出量は日本に自生する植物種を対象にして行なわれた近年の放出量測定結果を考慮して推定した。感度レジーム地理分布は，都心部およびその周辺のわずかな地域ではVOC-sensitiveであるが，その他の地域は，注意報発令レベルオゾンの出現日数が多い地域を含めて大部分がNOx-sensitiveであると推定された。一方，より小さめの既存の植物起源VOC排出量推定値を入力した場合のシミュレーション結果では，VOC-sensitiveの領域が顕著に多くなっており，植物起源VOC排出量の入力値によって感度レジームの推定結果が大きく左右されることがわかった。